Infectious Diseases of the Stomach in Immune-compromised Patients - Sang Min Lee; Dae Young Cheung (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
The gastrointestinal tract is a vast reservoir for internal microbiota; it is exposed directly to various externally introduced microbes, including bacteria, viruses, parasites and others. In immune-compromised conditions, the gastrointestinal tract is frequently affected by infectious diseases that seldom manifest clinically in immune-competent hosts. Immune-compromised conditions result from a variety of reasons, including human immunodeficiency virus infection, anti-cancer chemo-radiotherapy, immune suppressive therapy for autoimmune diseases, and organ transplantations. The stomach is a relatively rare site for opportunistic infections in immune-compromised patients compared to the esophagus and colon, where esophagitis and colitis develop frequently and cause significant clinical consequences. Helicobacter pylori infection is majorly involved in gastric malfunctioning in immune- compromised patients, followed by cytomegalovirus infection. Infections by Cryptosporidium, Mycobacterium avium complex, histoplasmosis, leishmaniasis, aspergillosis, or treponema, have been reported; however, gastric involvement of these agents is extremely rare. This review discusses the general aspects and recent reports on gastric infection in immune-compromised patients.